Teachers’ awareness of behavioural problems and mechanisms for dealing with them for early childhood (Study from kindergarten teachers’ destination in Hafar Al-Batin governorate) - Alaniz, Hana Mohammed Saier (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the extent to which kindergarten teachers are aware of early childhood behavioral problems and mechanisms for dealing with them. To achieve this goal, the study relied on the survey’s descriptive curriculum. The study tool was a questionnaire form applied to a sample of 163 kindergarten teachers in Hafar al-Batin governorate, to gather information on the questionnaire’s axes, namely: (The ability of kindergarten teachers to detect behavioral problems in early childhood, the awareness of kindergarten teachers of mechanisms to deal with behavioral problems in early childhood, obstacles to the application of methods to deal with and treat behavioral problems, programmers and mechanisms to prevent behavioral problems in early childhood). The results of the study There is a medium degree of agreement among the respondents on the awareness of female teachers to discover behavioral problems for early childhood in general, as the arithmetic mean (3.33), and this degree is considered medium for the awareness of kindergarten teachers on discovering behavioral problems for childhood premature, found that there were no statistically significant differences between the computational averages of teacher response on the axis of kindergarten teachers’ ability to detect early childhood behavioral problems across the variable years of experience where the value of the indicator level was greater than 0.05 and the absence of statistically significant differences between computational averages for the response of parameters on the axis of obstacles to dealing with behavioural problems according to the variable kindergarten type where the value of the indicator level was greater than 0.05. The study recommended the need to prepare qualification courses for kindergarten teachers to help them deal with behavioural problems of early childhood, giving more attention to students at this stage, as it is one of the most important stages influencing the construction and refinement of the child’s personality.